Leadership in the African context - Masango, Maake J. (Verbum et ecclesia, 2002)
The Western world has always viewed the African continent as plagued by corruption; dictatorship; military coups; rebellious leaders; greediness; misuse of power; and incompetent, politically unstable leaders - in effect, suspicious leaders who undermine their own democracies. This paper analyzes African leadership and its impact by concentrating on three historical eras, namely; the African Religious era; the Christian era, and the era of Globalization. These affected African leadership. In addition, many brilliant minds left the continent in search of greener pastures. A review of these three eras will help us understand how leadership shifted from African values into Western concepts. The role of missionaries lead African people to live with both an African and a Western concept of life. In spite of the above problems, our past leaders did their best in addressing the difficulties they faced during the three eras. African concepts of leadership were often regarded as barbaric and uncultured. Structures were evaluated by Western standards. Due to globalisation, African leaders, through programmes like NEPAD, are going back to basics, drawing on African concepts of unity among its leadership. Effectiveness or life-giving leadership is emerging and empowering villagers/communities in the continent. This type of leadership is innovative and has brought new hope for the continent.